КОНТРОЛІНГ РИЗИКІВ У БАНКУ: ТЕОРЕТИЧНИЙ АСПЕКТ (Світ фінансів, 2017)
Островська Н. С. Контролінг ризиків у банку: теоретичний аспект. Обґрунтовано необхідність формування контролінгу ризиків в комерційних банках України в період виходу з економічної кризи. З’ясовано, що використання послуг банківського контролінгу є поширеним у світі, але недостатньо розвиненим процесом в Україні для мінімізації банківських ризиків. Аргументовано, що контролінг ризиків потребує подальшого дослідження, аналізу та використання зарубіжного досвіду з урахуванням рівня розвитку банківської системи України. Островская Н. С. Контролинг рисков в банке: теоретический аспект. Обоснована необходимость формирования контролинга рисков в коммерческих банках Украины в период выхода из экономического кризиса. Выяснено, что использование услуг банковского контролинга – распространенный в мире, но не развитый процесс в Украине для минимизации банковских рисков. Аргументировано, что контролинг рисков нуждается в дальнейшем исследовании, анализе и использовании зарубежного опыта с учетом уровня развития банковской системы Украины. Ostrovska N. Controlling of risks in the bank: theoretical aspects. Introduction. The authors highlighted the theoretical aspects and the need for the formation of risks controlling in commercial banks of Ukraine in the period of economic crisis recovery. The use of banking controlling is a widespread process, yet it is not highly developed technique to minimize banking risks in Ukraine and a little attention is paid to expand these services. Therefore, this issue needs further investigation, analysis and use of foreign experience with account to the current level of banking system development in Ukraine for the improvement of bank management as a result of the research. Purpose. The existing problems of banking risks minimization give impetus to form the theoretical basis of the current practice of bank risks controlling organization, to identify scientific and methodological grounds for organizational functioning of the banking risks controlling system and to efficient subdivision of powers aimed at searching innovative ways towards improvement of the controlling services functioning based on the foreign experience regarding this issue.Results. Recenttrends of the banking system development in Ukraine and the economy as a whole have demonstrated that it is crucial to apply innovative and improved systems of management as well as the methodology of the managerial decision making. One of such systems is controlling. Banking Controlling is a system of managerial methods aimed at achieving the ultimate goals of the bank by means of making rational managerial decisions, the key elements of which are analysis, planning, control and information security.Conclusion. The implementation of banking risks controlling is becoming more and more up-to-date for the Ukrainian commercial banks that require significant innovations in the sphere of bank management and in the sphere of banking risks minimization. This issue is important since bank controlling is not merely managerial system, but the system that involves careful accounting, planning, marketing and budget control, it is by far the new way of thinking a manager must have to be able to analyze and forecast future actions. Controlling is aimed at maintaining the accepted level of bank risk by means of broad scope of tools and methods for its regulation and in case of the risk expansion its key task is to provide timely response in the specific situation and to develop grounded and economically reasonable recommendations for the bank management.